O Conselho Municipal dos Direitos da Criança e do Adolescente do município de Vitória da Conquista: espaço público de exercício da democracia participativa - Públio, Carlos Alberto Maciel (2009)
The objective of this research is to study the Conselho Municipal dos Direitos da Criança e do Adolescente (COMDICA) - City Council for the Rights of the Child and Adolescent - of the City of Vitória da Conquista-Bahia, since its implantation (1991) until the current days. The research was centered in the analysis of the COMDICA s capacity in influencing the public policies for infancy and adolescence as a privileged lócus to the exercise of the participatory democracy. In this view, the research was turned towards the understanding of the interlocutions quality of the Council with the City public power and with the institutions that take care of children and adolescents and also for knowledge of the technical level of the City s Council members on its functions as representants of the civil society and the ability of implementation of its deliberations. In conducting the research, it was evidenced that the COMDICA did not reach its objective as an instance that deliberates on public policies for infancy and adolescence. On the other hand, the city during the administrations of the Partido dos Trabalhadores party (PT), which corresponds to three mandates and, one third, in course, became truthfully a regional reference for implanting projects and developing actions (in the several areas) with the objective to reduce social inequalities and, over all, for assuring the children s and adolescent s rights in situation of social vulnerability